Financial Institutions and Markets across Countries and over Time : Data and Analysis - Beck, Thorsten; Demirgüç-Kunt, Asli; Levine, Ross (2012)
This paper introduces the updated and expanded version of the Financial Development and Structure Database and presents recent trends in structure and development of financial institutions and markets across countries. The authors add indicators on banking structure and financial globalization. They find a deepening of both financial markets and institutions, a trend concentrated in high-income countries and more pronounced for markets than for banks. Similarly, the recent increase in cross-border lending and debt issues has been concentrated in high-income countries, while low and lower-middle income countries have experienced an increase in remittance flows. Low net interest margins, rising profitability and declining stability in high-income countries banking sectors characterize the recent financial sector boom in high income countries leading up to the global financial crisis of 2007.